On the generation of chatter marks in peripheral milling: A spectral interpretation. (October 2018) - Grossi, N.; Scippa, A.; Sallese, L.; Montevecchi, F.; Campatelli, G.
Abstract: Chatter vibration induces a characteristic pattern on the milled surface, known as chatter marks, causing a poor surface quality. While several works deal with the prediction of the machined surface in stable condition, surface under chatter vibration has not been extensively studied: it is not clear how vibrations at high chatter frequency return highly spaced chatter marks on the surface. This paper investigates the chatter marks generation mechanisms focusing on this issue, i.e., on the surface spectral proprieties. The generation of the surface profile is regarded as a problem of sampling at the tooth pass frequency (in the time domain) and reconstruction (in the spatial domain) of the cutting tool displacements. Using this analogy, the paper highlights two main effects (aliasing and pseudo moiré), proposing specific formulations. The method is validated by a numerical investigation, based on a surface generation model coupled with a time-domain simulator of the milling process. Finally, an experimental validation is proposed. The formulations presented in this work provide an insight in the relation between chatter frequency and chatter marks pattern. Therefore, if the chatter frequency pattern over the spindle speed is known (e.g., identified via simulations or experiments), the proposed method could support the selection of cutting parameters which results in an acceptable surface, even in highly unstable cutting conditions. Highlights: An insight of the surface generation mechanism in milling is proposed. Surface profile is regarded as a problem of sampling at the ftp of the tool vibrations. Two fundamental spatial frequencies are identified, composing chatter marks surface. Formulations to predict spectral proprieties of chatter marks are provided. Numerical and experimental tests prove the accuracy of the proposed approach.